Nuevos estudios de citogenética convencional al servicio de pacientes del departamento de Boyacá. - Vergara Estupiñán, Edwin Javier; Forero Castro, Ruth Maribel (Uptc, 2012)
Conventional cytogenetics allows diagnosing numerical and structural chromosomal abnormalities, as they  to rescue the studies of conventional cytogenetics that have been serving the population of Boyacá and that  Molecular Biology. Interdisciplinary studies developed by Sánchez and Corredor (2010) and Vergara (2011)  respectively, benefiting 25 patients, as diagnostics and consultation had no charge to the patients, also it was  cytogenetics in Boyacá.